How do physicians cope with controversial topics in existing guidelines for the management of infective endocarditis? Results of an international survey. (February 2016) - Béraud, G.; Pulcini, C.; Paño-Pardo, J.R.; Hoen, B.; Beovic, B.; Nathwani, D.; ,
Abstract: International guidelines are available to help physicians prescribe appropriate antibiotic regimens to patients with infective endocarditis (IE). However some topics of these guidelines are controversial. We conducted an international survey to assess physicians' adherence to these guidelines, focusing on these controversial items. An invitation to participate to a 15-question online survey was sent in 2012–2013 to European Society of Clinical Microbiology and Infectious Diseases (ESCMID) members, scientific societies and corresponding authors of publications on IE mentioned in PubMed from 1990 to 2012, inclusive. Eight hundred thirty-seven physicians participated in the survey, and 625 (74.7%) completed it over the first question. The results showed great heterogeneity of practices. Claiming to follow guidelines was marginally associated with more guideline-based strategies. Gentamicin use depended on causative pathogens (p <0.001) and physician specialty (p 0.02). Eighty-six per cent of the physicians favoured vancomycin alone or in combination with gentamicin or rifampicin as a first-line treatment for left-sided native valve methicillin-resistant Staphylococcus aureus IE, 31% considered switching to oral therapy as a therapeutic option and 33% used the ampicillin and ceftriaxone combination for enterococcal IE as a first-line therapy. Physician specialty significantly affected the choice of a therapeutic strategy, while practicing in a university hospital or the number of years of practice had virtually no impact. Our survey, the largest on IE treatment, underscores important heterogeneity in practices for treatment of IE. Nonetheless, physicians who do not follow guidelines can have rational strategies that are based on the literature. These results could inform the revision of future guidelines and identify unmet needs for future studies.